The Effect of Various Supplementary Irrigation Treatments on Plant and Soil Moisture Relationships in a Vineyard (Vitis Vinif era var. Chenin Blanc) - Van Zyl, J. L.; Weber, H. W. (South African Journal of Enology and Viticulture, 2017)
In a field plot trial with grape vines planted on a high potential soil, the soil moisture status on different irrigation treatment plots was compared with that of a dryland control. Soil moisture budgeting was based on physical soil properties and root distribution patterns before treatments commenced. A maximum concentration of roots occurred at the 300-450 mm depth zone, while approximately 90 per cent of the total number of roots was found above 900 mm. Tensiometric readings of soil moisture potential, supplemented by electrometric resistance readings from gypsum blocks, indicated complete depletion between veraison and harvesting of the total available moisture on dryland plots. Despite this severe moisture stress as illustrated by chrono-isopletes, a reasonably good grape yield was still produced by the dryland vines, indicating either exceptional drought resistance or the uptake of water from extraneous sources. Supplementary irrigations greatly improved soil moisture conditions during the important growth stages of (a) flowering and fruit set, (b) green berry stage and (c) veraison. Moisture depletion patterns changed markedly as the season progressed from November to January, and as naturally stored rain water became depleted. In contrast to the absorption pattern in November, the fastest rate of water loss occurred in the deepest root zones during January, because of unsaturated moisture flow into the dry partly decomposed parent material. The apparently unproductive subsoil might act as a large natural reservoir for superfluous winter rain, which in summer becomes available to the vines through unsaturated upward flow into the root zone. Determination of leaf water potential showed unexpectedly high values at night (minima of -283kPa) in plants growing in soil of which the major part was dried below wilting point. Vines were thus able to regain turgidity at night. Crop factors for use with the American Class A-pan for scheduling irrigations were calculated. Crop factors were low (November to February = 0,20-0,30), and again emphasised the ability of vines to use water frugally. Crop factors were strongly dependent upon soil moisture conditions. Empirical coefficients for use in the Blaney-Criddle formula are also presented.